2009
DOI: 10.1002/ptr.2937
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity effect of baicalin involves the modulations of proadipogenic and antiadipogenic regulators of the adipogenesis pathway

Abstract: In this study, the antiobesity effects of baicalin, 5,6-dihydroxyflavone-7-glucuronic acid, were characterized using an in vitro system of adipogenesis, i.e. fat cell formation. Baicalin-treatment of 3T3-L1 preadipocytes was shown to inhibit triglyceride accumulation and lipid droplet formation during induced adipogenesis. Microarray analyses showed that baicalin modulated the expression of genes located in pathways such as adipogenesis, cholesterol biosynthesis, focal adhesion and others. In the adipogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
4
26
0
1
Order By: Relevance
“…Natural flavonoids, found in various plants and herbal medicines, up-or down-regulate differentiation of 3T3-L1 preadipocytes and gene expression involved in adipogenesis. [24][25][26][27][28] In our study, we found that the flavonoid kaempferol is potent in repressing both lipid accumulation and expression of adipogenic markers. Kaempferol is found in many medical plants, such as Gingko biloba (Gb), Pinus densiflora SIEB.…”
Section: Discussionsupporting
confidence: 49%
“…Natural flavonoids, found in various plants and herbal medicines, up-or down-regulate differentiation of 3T3-L1 preadipocytes and gene expression involved in adipogenesis. [24][25][26][27][28] In our study, we found that the flavonoid kaempferol is potent in repressing both lipid accumulation and expression of adipogenic markers. Kaempferol is found in many medical plants, such as Gingko biloba (Gb), Pinus densiflora SIEB.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, much interest has been focused on the discovery of safe and effective natural products capable of regulating adipogenesis and fat accumulation (Hassan et al, 2007;Lee et al, 2009;Saito et al, 2008;Zhang et al, 2009). In our previous study, we demonstrated that shikonin, a natural compound isolated from Lithospermun erythrorhizon Sieb.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, polymethoxyflavonoids and sakuranetin isolated from Kaempferia parviflora and Smallanthus fruticosus, respectively, enhanced adipocyte differentiation via GATA-2 mRNA expression [26,27]. Platycodin D from Platycodon grandiflorus and baicalin from Scutellaria baicalensis have been reported to inhibit adipogenesis via upregulating KLF2 and via upregulating KLF2 and downregulating KLF15 mRNA levels, respectively; mRNA levels were measured at 2-7 days after induction [28,29]. These reports indicated that some members of the GATA and KLF families are key regulators of adipocyte differentiation at an early stage (~2 days after induction).…”
Section: Discussionmentioning
confidence: 99%